The Weight Distributions of the Duals of Cyclic Codes With Two Zeros - Ding, Cunsheng; Liu, Yang; Ma, Changli; Zeng, Liwei (IEEE transactions on information theory, 2011)
Cyclic codes with two zeros and their dual codes have been a subject of study for many years. However, their weight distributions are known only for a few cases. In this paper, the weight distributions of the duals of the cyclic codes with two zeros are settled for a few more cases.